PENGARUH STORE PLANNING, MERCHANDISING DAN KERAGAMAN PRODUK TERHADAP KEPUTUSAN PEMBELIAN DI TOKO BUKU GRAMEDIA (STUDI KASUS PADA KONSUMEN TOKO BUKU GRAMEDIA PANDANARAN SEMARANG) - Dian Nur Cahyani; Saryadi Saryadi; Widiartanto Widiartanto (Jurnal Ilmu Administrasi Bisnis, 2015)
The background of the research is the growth of the retail business in Indonesia. It is shown by the number of new retail businesses that appear and compete within the market. Each company would want its business to survive, and to grow over the time and earn some profit, therefore, Gramedia Bookstore has to think of a way to stay survive and attract more customers. Specifically the research discusses about Gramedia Pandanaran Semarang Bookstore which within 2011 – 2013 has had decreasing number of customers to do transaction. Should the condition remain and is not overcome, it is highly likely that there will be bigger problem for Gramedia Pandanaran Semarang Bookstore. The objective of the research is to recognize the influence of store planning, merchandising, and product variationtowards the purchasing decision in Gramedia Pandanaran Semarang Bookstore. The type of the research is explanatory, using data collecting technique of questionnaire and interview. Sampling technique is non-probability sampling using Purposive Sampling. The sample is 100 customers of Gramedia Pandanaran Semarang Bookstore who had purchased at least twice. The research uses qualitative and quantitative data analysis. Quantitative analysis uses validity test, reliability test, correlation coefficient, simple and multiple linear regression analysis, determination coefficient, significance test (t test and f test). The result of the research shows that entirely Store Planning influences the Purchasing Decision with beta coefficient value of 0.555 and determination coefficient for variable Store Planning (X1) contributes 30.1% towards the variable of Purchasing Decision and the remaining 69.9% is explained by other factor other than variable Store Planning. There an influence between Merchandising towards Purchasing Decision with beta coefficient value of 0.530 and determination coefficient for variable Merchandising (X2) contributes 27.3% towards Purchasing Decision variable (Y) and the remaining 72.7% is explained by other factors other than variable Merchandising. There is an influence between Product Variety and the Purchasing Decision with the value of coefficient beta. Of 0.525 and the determination coefficient for Product Variety variable (X3) contributes 26.8% towards purchasing decision and the remaining 73.2% is explained by other factor other than Product Variety variable. The conclusion of the research is that between Store Planning and Merchandising and Product Variation has positive and significant influence towards Purchasing Decision. It suggeststhat Gramedia Bookstore has to improve the innovation in fulfilling the need of the customers through the way of presenting the product and the vast variation of product.